Innovative Teaching and Learning through Open Educational Resources - Amalia Venera TODORUT (Communications of International Proceedings, 2021)
The profound transformations, the speed of change, the complexity and the crisis of Covid 19 are the attributes of today's society that reflects on education, imposing a reconfiguration of it in the era of digital technology. The fundamental objective of the paper is to highlight the importance of rethinking digital education from the perspective of innovation and also the idea of promoting education for innovation during the pandemic and post-pandemic. Thus, in the current context, open education is of special importance, which aims to widen access and participation of all by removing barriers and creating accessible and personalized learning for all. During the paper we characterized the dimensions of open education: strategy, quality, leadership, access technology, content, pedagogical aspect, collaboration, research. The scientific investigation is materialized in the study and comparative analysis of the data and information contained in the studies and scientific articles in the literature, as well as by exploring the official sites specific to this field. The scientific research undertaken is also based on the interpretation of questionnaires applied to students and teachers, to identify challenges and find solutions for quality education in a pandemic and post-pandemic context.
Keywords: Digital education; innovation; creativity; open education; digital thinking